Histories and stories from Chiapas : border identities in Southern Mexico - Hernández Castillo, Rosalva Aída (University of Texas Press, 2001)
The 1994 Zapatista uprising of Chiapas' Maya peoples against the Mexican government shattered the state myth that indigenous groups have been successfully assimilated into the nation. In this wide-ranging study of identity formation in Chiapas, Aiacute;da Hernaacute;ndez delves into the experience of a Maya group, the Mam, to analyze how Chiapas' indigenous peoples have in fact rejected, accepted, or negotiated the official discourse on "being Mexican" and participating in the construction of a Mexican national identity. Hernaacute;ndez traces the complex relations between the Mam and the national government from 1934 to the Zapatista rebellion. She investigates the many policies and modernization projects through which the state has attempted to impose a Mexican identity on the Mam and shows how this Maya group has resisted or accommodated these efforts. In particular, she explores how changing religious affiliation, women's and ecological movements, economic globalization, state policies, and the Zapatista movement have all given rise to various ways of "being Mam" and considers what these indigenous identities may mean for the future of the Mexican nation. The Spanish version of this book won the 1997 Fray Bernardino de Sahaguacute;n national prize for the best social anthropology research in Mexico